LASER FORMING OF METALLIC DOME-SHAPED PARTS USING SPIRAL AND RADIAL-CIRCULAR SCAN PATHS - Safari, Mehdi (Journal of Advanced Manufacturing Technology (JAMT), 2016)
A new application of the laser forming process is production of dome-shaped parts as a prototype. For the production of curved parts, especially for the dome -shaped ones, different strategies have been developed which are mostly based on curved irradiation paths. In this paper, a circular-radial strategy of scanning path to form dome shapes by using laser is investigated. Furthermore, experiments have been carried out to validate the numerical results. Finally, a new scanning pattern is presented as a spiral strategy. It is shown that the stress distribution is more uniform in laser forming with the use of spiral scanning path. In addition, the deformed parts with spiral scanning path are more uniform compared to other investigated scanning paths. Furthermore, it is found that laser forming with radial-circular scan paths will result in buckling mechanism whereas spiral irradiation will lead to gradient mechanism. Finally, thickness distribution and temperature gradient of the deformed parts caused by different laser paths are investigated.